SEMUT RANGRANG DALAM KARYA SENI GRAFIS TEKNIK STENCIL PRINT - Eki Wirahman; Ariusmedi Ariusmedi; Yofita Sandra (Serupa The Journal of Art Education, 2020)
This final work visualizes the rangrang Ant in the form of graphic art, to be able to shape social behavior. The visualization of the rangrang ant is expected to be able to have a positive influence, on the lives of oneself and society, through graphic print art (serigraphy). The methods and processes used in the creation of a work include several stages: (1) preparation; (2) elaboration; (3) synthesis; (4) concept realization; (5) finising; discussion of graphic art works includes visualization of Semr rangrang. The titles of the work produced are: (1) Queuing; (2) Strong; (3) Interaction; (4) Responsibility; (5) Smart; (6) Trying to; (7) Believe; (8) Working; (9)Concern;(10)Sharing;Kata Kunci : semut rangrang, seni grafis,